ANALISIS DAYA DUKUNG DAN PENURUNAN PONDASI PADA PEMBANGUNAN JALUR GANDA KERETA API - yonas prima arga rumbyasro marpaung; Bermando Mangatur Siagian; Muhammad Arief Aldianto (Fakultas Teknik Universitas Krisnadwipayana, 2022)
Given that the project site is in a highly populated area and has a geological conditionof soil with a relatively high water content, the borepile foundation is the best option. Thepurpose of this study is to compare settlement estimates made manually and using the Plaxis3D application, as well as to examine the bearing capability of the borepile foundation utilizingsondir data and conventional penetration tests. The research methodology used to write thisfinal project was a case study, and it involved observation as the primary data collection tool.Using the Mayerhoff method, the following values were determined for the borepile bearingcapacity: Qult = 152.403 tons, Qijin = 32.15527, Qtotal = 718.4571, and Qijin = 160.4381.and for SPT data using the Reese & Wright method at borepile point A18 obtained Qu =1163.89 tons, and Qijin = 387.964 tons. In the manual method of the semi-empirical methodand the vesic method for the analysis of the single borepile drop at point A18, S = 15 mm andS = 12.8 mm, respectively. The output of the Plaxis 3D program is S = 19.2 mm, and the PDAtest results are achieved. S = 5mm. The results of the settlement analysis, which was performed,have complied with SNI 8460: 2017's standards for foundation settlement, which is 25 mm